Human well-being and the natural environment - Dasgupta, Partha (New York : Oxford University Press, 2004)
In Human Well-Being and the Natural Environment, Partha Dasgupta explores ways to measure the quality of life. Although the problem pervades a number of academic disciplines, it is not confined to the academic realm. International organizations regularly publish cross-country estimates of the quality of life, journalists and commentators publicize them, and national governments are obliged to take note of them. Today, quality-of-life indices broker political arguments and together form a coin that even helps purchase economic and social policy."--Jacket
Includes references and index
Keywords: Sustainable development; Natural resources -- Management; Human ecology